2011
DOI: 10.1111/j.1834-7819.2011.01329.x
|View full text |Cite
|
Sign up to set email alerts
|

Different powered toothbrushes for plaque control and gingival health

Abstract: Background: Powered brushes were first introduced commercially in the 1960s. A recent systematic review suggested the superiority of certain modes of powered over manual toothbrushing for plaque and gingivitis reduction. That review did not allow for direct comparison between different modes of powered toothbrush. Objectives: To compare different modes of powered toothbrushing against each other for plaque reduction and the health of the gingivae. Other factors to be assessed were calculus and stain removal, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 8 publications
0
47
0
3
Order By: Relevance
“…[36][37][38] Systematic reviews have demonstrated that powered toothbrush was more effective for removing plaque and reducing gingivitis. [18][19]39 Moreover, there was no significant cause-and-effect relationship between the use of powered toothbrushes and soft tissue injury, and the reports of soft tissue injury were rare 40 . The safety of using powered toothbrush was reliable, tissue damage was only a small probability of events, and powered toothbrushes are just as safe as manual ones.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Systematic reviews have demonstrated that powered toothbrush was more effective for removing plaque and reducing gingivitis. [18][19]39 Moreover, there was no significant cause-and-effect relationship between the use of powered toothbrushes and soft tissue injury, and the reports of soft tissue injury were rare 40 . The safety of using powered toothbrush was reliable, tissue damage was only a small probability of events, and powered toothbrushes are just as safe as manual ones.…”
Section: Discussionmentioning
confidence: 99%
“…Main findings in the context of the existing evidence, interpretation Although power toothbrushes with varying modes of operation are widely available (eg, sonic, side-to-side action), meta-analyses from the Cochrane Review Group have concluded that a single class-oscillating-rotating power toothbrushes-has substantiated greater reductions in plaque and gingivitis than side-to-side electric brushes and standard manual toothbrushes. 19,20 The power toothbrush used in the present study is in the family of oscillating-rotating power toothbrushes with statistically and clinically significant antiplaque and antigingivitis benefits documented in more than 250 laboratory and clinical published investigations. 21 Expanding on this established efficacy, the novel technology platform used in this clinical trial combines the interactive oscillating-rotating brush with Bluetooth technology.…”
Section: Discussionmentioning
confidence: 99%
“…Power (electric) toothbrushes have been evaluated across a broad array of population groups and study designs and have demonstrated similar or significantly greater (for the oscillating-rotating class) plaque removal compared with standard manual toothbrushes. [19][20][21][22][23][24][25][26] Some additionally offer options for targeted needs, such as orthodontic brush heads to improve interbracket cleaning.…”
mentioning
confidence: 99%
“…For example, in the UK, over 25% of households now contain a power toothbrush, while the equivalent figure in Germany is over 33% (manufacturer data). Research data on O/R power toothbrushes have been independently reviewed by the Cochrane Collaboration , who found evidence supporting the benefits of this type of power brushing technology for the reduction in plaque and gingivitis.…”
Section: Discussionmentioning
confidence: 99%
“…side‐to‐side or oscillating–rotating) . Many clinical studies have assessed the comparative clinical effectiveness of the various models, and a well‐documented comprehensive review of the results of comparative clinical studies has shown plaque control advantages for power brushes over manual toothbrushes, but only those power toothbrushes that have an oscillating–rotating action have shown consistent short‐ and long‐term benefits for plaque removal and gingivitis reduction .…”
Section: Introductionmentioning
confidence: 99%